ANALISIS DIGITALISASI INDUSTRI, PENCIPTAAN KESEMPATAN KERJA DAN TINGKAT PENGANGGURAN TERBUKA DI INDONESIA - I Gusti Ayu Diah Dhyanasaridewi (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
Opposition to the positive and negative effects of industrial digitalization on the unemployment rate occurs in society. There are two forms of concern about the negative effects of digitalization that can eliminate employment opportunities, namely the first will be the replacement of human work in the production process by smart robots as a result of digitizing production, and the second concern that jobs will be lost due to takeovers by part-time workers according to the needs and digital business platform. This concern is not proven because historically the level of unemployment has not been influenced by the industrial revolution that took place. Indeed there are types of jobs that are lost, but new types of jobs always emerge that absorb more labor. The community only needs to prepare themselves and adapt to the changes that occur, supported by government policy